Attentional Cueing and Executive Deficits Revealed by a Virtual Supermarket Task Coupled With Eye-Tracking in Autism Spectrum Disorder - Mouga, Susana; Duarte, Isabel Catarina; Café, Cátia; Sousa, Daniela; Duque, Frederico; Oliveira, Guiomar; Castelo-Branco, Miguel (Frontiers in Psychology, 2021)
Executive functioning (EF) impairments in Autism Spectrum Disorder (ASD) impact on complex functions such as social cognition. We assessed this link between EF, attentional cueing, and social cognition with a novel ecological task (“EcoSupermarketX”). Our task had three blocks of increasing executive load and incorporated social and non-social cues, with different degrees of saliency. Performance of ASD and typical neurodevelopment was compared. ASD showed a significant performance dependence on the presence of contextual cues. Difficulties increased as a function of cognitive load. Between-group differences were found both for Social and Non-Social salient cues. Eye-tracking measures showed significantly larger fixation time of salient social cues in ASD. In sum, EcoSupermarketX is sensitive to detect EF and attentional cueing deficits in ASD.